2016
DOI: 10.1007/s00268-016-3557-3
|View full text |Cite
|
Sign up to set email alerts
|

A Positive Node on Ultrasound‐Guided Fine Needle Aspiration Predicts Higher Nodal Burden Than a Positive Sentinel Lymph Node Biopsy in Breast Carcinoma

Abstract: Patients with positive USFNAC have more aggressive clinico-pathological characteristics and higher nodal burden compared to SLNB-positive patients. Currently, the authors advocate that patients not receiving neoadjuvant chemotherapy, with a positive USFNAC, should proceed directly to an axillary ALND.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 36 publications
7
22
0
Order By: Relevance
“…However, in our series of 72 patients with nonpalpable axillary nodes, positive FNAC, T1‐2 primary tumor and breast‐conserving surgery, 22 (31%) showed less than three metastatic axillary nodes, therefore fitting with ACOSOG Z0011 criteria and would have avoided axillary dissection . Other studies have found similar results …”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…However, in our series of 72 patients with nonpalpable axillary nodes, positive FNAC, T1‐2 primary tumor and breast‐conserving surgery, 22 (31%) showed less than three metastatic axillary nodes, therefore fitting with ACOSOG Z0011 criteria and would have avoided axillary dissection . Other studies have found similar results …”
Section: Discussionsupporting
confidence: 67%
“…Boland et al found that the FNAC‐positive patients, compared to the positive SLNB group, are more likely to undergo mastectomy (53.8% vs 35.5%, P < .001). In the FNAC‐positive group more aggressive tumor characteristics were found: a higher median tumor grade (3 vs 2; P < .001) and a higher frequency of Her‐2/neu amplification (25% vs 12.6%; P < .001) . Verheuvel et al published similar results with a higher proportion of mastectomies in FNAC‐positive patients than in SLNB‐positive group (64.7% vs 31.3%, P < .001), because of larger tumors (≥ 20 mm 83% vs 41.8%, P < .001), with worse prognostic factors: high tumor grade (G3 27% vs 18%, P < .001) and Her‐2/neu amplification (18.7% vs 8%, P < .006).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…21 Pilewskie et al showed that positive FNAC was insufficient to warrant AD because 47% had only 1 to 2 metastatic LNs. Previous studies also showed that FNAC-positive patients had more aggressive clinicopathological characteristics and higher nodal burden than SLNB-positive patients, with the median number of involved LNs being 3 in FNAC-positive patients vs 1 in SLNB-positive patients.…”
Section: Resultsmentioning
confidence: 99%